Practice makes progress: essential components in digital health training for current and prospective health workers - Laura Thomas; Amy Braddon; Crystal Lee; Richard Norman; Kate Valmadre; Stephanie Waters; Giles Nunis; Tab Berger; Suzanne Robinson (Discover Education)
Abstract This study explored whether digital health content was included in current higher education curriculum, barriers and enablers to inclusion, key skills required and university educators' confidence in delivering content in undergraduate and postgraduate health courses in Western Australia. A three-stage design included: 1) desktop audit of course (n = 117) and unit (n = 1559) descriptors for digital health-related keywords; 2) semi-structured interviews with university educators (n = 15); and 3) online survey of final year students (n = 14). Health, allied health, medicine, nursing and midwifery disciplines at five universities were included. The audit identified limited digital health-related keywords. Interviews identified unsystematic application of digital health content across disciplines. Five themes for digital health curriculum were identified; only one required discipline-specific content. Despite low responses, students supported a need for additional training opportunities to support digital health skill implementation in practice. Comprehensive and ongoing digital health curricula and practice opportunities are needed for undergraduate and postgraduate health workers. Consideration should be given to the skills of university educators and clinical supervisors regarding their own confidence in delivering digital health teaching and practice opportunities for students. A universal approach, supplemented by discipline-specific content, may create efficiencies in curriculum development and support a common language and understanding across professions.